2006
DOI: 10.1016/j.ygeno.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reelin gene polymorphisms with autism

Abstract: Genome scans indicate a linkage of autism to the chromosome 7q21-q36 region. Recent studies suggest that the Reelin gene may be one of the loci contributing to the positive linkage between chromosome 7q and autism. However, these studies were relatively small scale, using a few markers in the gene. We investigated 34 single nucleotide polymorphisms (SNPs) in the Reelin gene with an average spacing between the SNPs of 15 kb for evidence of association with autism. There were significant differences in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 48 publications
3
68
0
2
Order By: Relevance
“…The most commonly assessed variant in RELN is a trinucleotide repeat polymorphism in the 5 0 UTR with unknown functional relevance. Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD.…”
Section: Chromosomementioning
confidence: 86%
See 1 more Smart Citation
“…The most commonly assessed variant in RELN is a trinucleotide repeat polymorphism in the 5 0 UTR with unknown functional relevance. Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD.…”
Section: Chromosomementioning
confidence: 86%
“…However, in another study, 178 the most common repeat 10 was over-represented in AD. One study 177 reported an association of the more common allele of SNP rs736707, which has not yet been replicated by other studies and might not be of functional relevance, as it is located in intron 59 of RELN. Despite the biochemical evidence of a possible role of Reelin in the pathogenesis of autism, the genetic findings are still inconsistent.…”
Section: Chromosomementioning
confidence: 92%
“…In addition, a number of other immunerelated genes have been implicated in ASD, including macrophage migration inhibitory factor (MIF), 43 MET encoding tyrosine kinase, 44 the serine and threonine kinase C gene PRKCB (alias PRKCB1), 45 protein phosphatase and tensin homolog (PTEN), 46 and the reelin gene (RELN). [47][48][49] It is not known whether immune activation plays an initiating or ongoing role in the pathology of ASD. Immune activation leading to inflammation can have serious detrimental effects and could lead to destruction of tissues.…”
Section: Autoimmunity and Immune Dysfunction In Individuals With Asdmentioning
confidence: 99%
“…Genetic studies in human populations have suggested that the RELN gene may be associated with autism susceptibility, [146][147][148][149] although not all findings have been positive. [150][151][152] Fatemi et al 153,154 have shown that levels of RELN mRNA and Reelin protein are significantly deficient in the brain of autistic subjects.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%